A Framework for Real-time Spatial Labor Data Analytics from Construction Sites - Abouorban, Hoda (AUC Knowledge Fountain, 2022)
In construction, the field of real-time monitoring and control of on-site resources is still evolving. In recent years, there has been an increasing demand for improved real-time monitoring systems on construction sites. Such technologies are widely employed in domains such as IT monitoring and the healthcare industry. The construction industry, on the other hand, has yet to recognize the value of implementing real-time monitoring systems on building sites. There is limited research in the area of using real-time monitoring, such as RFID tags and Visual Sensing, for the control of on-site safety performance and labor and earthmoving equipment productivity. Many of the studies focus on analyzing the data gathered, with the information only being used to verify the accuracy of the real-time monitoring technologies employed. The purpose of this study is to reveal the potential outcomes that can be obtained by collecting and analyzing real-time data about worker locations on a construction site. The results are obtained by creating a semi-automated framework that analyses the collected real-time data. The framework consists of three steps. To begin, site data is semi-automatically collected, and spatial data from real-time workers is obtained using GPS tracking technologies. In the second step, the data is prepared for processing. Third, to examine the prepared data, visual and spatial-temporal analysis techniques are used. After that, the proposed framework is tested on a theoretical set of data for the first order of data analysis. The framework's implementation outputs are then used for second-order analysis, where the individual outputs are compared to each other. The results are compared to identify any existing relationships between the various site parameters. The goal of second-order analysis is not to quantify or define the relationships, but rather to provide a means of comparison for identifying potential relationships. Finally, the framework is applied for workers’ spatial data collection and analysis on a case study for a construction site in Cairo, Egypt. The outputs of the framework highlight the potential benefits of deploying real-time technologies on construction sites. As a result of this research, stakeholders now have access to a framework that collects and analyses data from construction sites in order to improve site performance monitoring and control.